2013
DOI: 10.1016/j.foodres.2013.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural (grape seed and chestnut extract) and synthetic antioxidants (buthylatedhydroxytoluene, BHT) on the physical, chemical, microbiological and sensory characteristics of dry cured sausage “chorizo”

Abstract: Antioxidant activity of grapeseed and 2 chestnut extract in dry-cured sausage "chorizo" 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 44 publications
13
113
0
12
Order By: Relevance
“…The seaweed and chestnut extracts were not effective at increasing the product's oxidative stability. 99 Despite the fact that chestnut did not show antioxidant activity in these studies, a previous study by Lorenzo et al 100 concluded that chestnut extract had antioxidant activity in dry-cured sausages.…”
Section: Antioxidant Compounds Derived From Fruit Processingmentioning
confidence: 79%
See 2 more Smart Citations
“…The seaweed and chestnut extracts were not effective at increasing the product's oxidative stability. 99 Despite the fact that chestnut did not show antioxidant activity in these studies, a previous study by Lorenzo et al 100 concluded that chestnut extract had antioxidant activity in dry-cured sausages.…”
Section: Antioxidant Compounds Derived From Fruit Processingmentioning
confidence: 79%
“…Many studies have wileyonlinelibrary.com/jsfa 91 Shan et al, 166 Rojas and Brewer, 96 Sasse et al, 102 Brannan, 97 Pateiro et al, 98 Lorenzo et al, 100 Lorenzo et al 99 …”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the GSE can be used as a natural food additive due to high antimicrobial and antioxidant activities (Hogan et al, 2001;Kulkarni et al, 2011;Lorenzo et al, 2013;Peng et al, 2010). Gokoglu and Yerlikaya (2008) also found that GSE had inhibition effect on the formation of melanosis of Parapenaeus longirostris stored at 4℃ for 3 days by sensory analysis and color measurements.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, there has been a recent attention on the use of natural phenolic compounds due to their antioxidant properties and potential health effects (Anagnostopoulou et al, 2006;Rahmanian et al, 2014;Taghvaei, et al, 2015). Several studies have been conducted with the target of protecting foods against oxidation by using natural antioxidants such as grape seed extract, chestnut, rosemary, green tea, etc (Lorenzo et al, 2013;Gibis and Weiss, 2012;Samotyja and Malecka, 2007).…”
Section: Introductionmentioning
confidence: 99%